2018
DOI: 10.3389/feduc.2018.00048
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors of Child's Bully and Victim Statuses: A Longitudinal Investigation Using Parent, Teacher, and Student Reports From National Data

Abstract: Although bullying is known to have detrimental effects, less is known regarding how these bullies and victims develop within the contexts of their homes and schools, and how early childhood behaviors can predict later bullying/victimization statuses. Parent, teacher, and student reports from the Early Childhood Longitudinal Study-Kindergarten (ECLS-K) 1998-1999 cohort (N = 11,715) representing a nationwide sample of children, were utilized to predict child's bully and victim status in eighth grade (age 13-14) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…On the other hand, other studies have found that high responsiveness and affection protect adolescents from peer victimization [16,18] because parental affection and warmth encourages a positive parent-child communication and disclosure [32,39]. Furthermore, positive family relationships, characterized by high parental involvement, family support, positive communication, and cohesion, are related to a reduced risk for engaging in peer aggression [11,15,40] and victimization [31], while bully-victims reported lower levels of parental support compared to aggressors and victims [41].…”
Section: Parenting Dimensions and Peer Aggressionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, other studies have found that high responsiveness and affection protect adolescents from peer victimization [16,18] because parental affection and warmth encourages a positive parent-child communication and disclosure [32,39]. Furthermore, positive family relationships, characterized by high parental involvement, family support, positive communication, and cohesion, are related to a reduced risk for engaging in peer aggression [11,15,40] and victimization [31], while bully-victims reported lower levels of parental support compared to aggressors and victims [41].…”
Section: Parenting Dimensions and Peer Aggressionmentioning
confidence: 97%
“…The quality of family relations plays an important role in the development of aggression and victimization in adolescents [11]. Research on parenting and peer aggression has been mainly focused on parenting dimensions and parenting styles [12][13][14].…”
Section: Parenting Dimensions and Peer Aggressionmentioning
confidence: 99%
“…Low level of empathy, moral distancing, low awareness of the threat of media messages, in the Internet, problems with emotional regulation, or low level of family support are factors indicated as the main predictors of bullying agency (12)(13)(14). However, very interesting is the fact that among the individual risk factors of this type of behavior, the importance of low self-esteem, low level of social skills, with deficiencies in social information processing, and low sociometric status in the peer group is indicated (15,16). Such factors also turn out to be important in the development of experiences as victims of bullying.…”
Section: Risk Factors and Protective Factors Of Bullyingmentioning
confidence: 99%
“…Noteworthy is the longitudinal study by Natesan et al (16), carried out on a large sample (n = 11,715), which collected data from children, teachers, and parents. The results obtained by authors indicated that internalizing behaviors are a predictor of being a victim of school violence, while externalizing behaviors and passive communication between parents (mutual criticism, inhibition of discussion, not talking to each other) are a predictor of being a school aggressor.…”
Section: Risk Factors and Protective Factors Of Bullyingmentioning
confidence: 99%
“…[22][23][24][25] A child exposed to bullying behavior can be both a bully and a victim by applying this behavior to the person he/she can afford. 26,27 A positive parental attitude results in adolescents' positive behaviors when viewed from the perspective of risky health behaviors. [28][29][30] A positive relationship between children and their parents can protect against threats in cyber.…”
mentioning
confidence: 99%